Political Brokers in Head of Village Elections (A Case Study in Sangal Village and Rantau Bangkiang Village, Central Kalimantan Province, Indonesia) - Pioh, Novie Revlie; Palenewen, Jovano Deivid; Bataha, Katerina (Universitas Muhammadiyah Yogyakarta, 2024)
This study delves into the phenomenon of political brokers influencing village head elections in Sanggal Village and Rantau Bangkiang Village, Central Kalimantan Province, Indonesia. It employs the concepts of political brokers,patron-client relationships, and various forms of patronage to analyze how candidates utilize brokers to distribute resources and garner public support. Adopting a qualitative approach with a case study design, the research sheds light on the previously unexplored presence of political brokers within the context of village head elections, which have traditionally been seen as less susceptible to such influences compared to regional or national elections. The findings reveal a critical role played by political brokers in securing victories for village head candidates. Interestingly, the study also identifies a deviation from the typical material-based exchange, demonstrating that brokers may be motivated by less tangible benefits or even act as volunteers. This research contributes to a more comprehensive understanding of power dynamics within village head elections by highlighting the previously overlooked role of political brokers. It raises questions about the evolving nature of political influence at the local level and the potential implications for village governance and development.